Analisis Mekanisme dan Penerapan Pengelolaan Dana Pensiun Syariah Terhadap Fatwa DSN-MUI NOMOR 88/DSM-MUI/XI/2013 Pada Bank BTPN Syariah - Alivia Nurhasanah; Wirman Wirman (Peneliti.net, 2023)
This study intends to determine the System and Implementation of Sharia Annuity Assets for administrators according to the DSN MUI Fatwa Number 88/DSN-MUI/XI/2013 at Bank BTPN Syariah. This research uses a qualitative descriptive case study research. According to the author's analysis, the results of the Sharia Pension Fund Management Mechanism at Bank BTPN Syariah are very straightforward. Starting with a salary transfer from Bank BTPN Syariah to PT TASPEN. From there the customer has the option to choose Sharia Pension Fund Services at Bank BTPN Syariah, such as financing through a Murabahah or Ijarah contract or a Pension Payment Partner through Mudharabah Muthlaqah Implementation of Sharia Pension Fund Management in accordance with DSN MUI Fatwa Number 88/DSNMUI/XI/2013 at the Bank Sharia BTPN, except for PT TASPEN participant membership provisions.